INSTRUCTIONAL LANGUAGE IN KAHOOT!-BASED EFL LEARNING: A QUASI-EXPERIMENTAL STUDY IN INDONESIAN SECONDARY SCHOOLS - Suyitno; Khoirul Anwar (Indonesian EFL Journal, 2026)
This mixed-methods study with a quasi-experimental design examined students' engagement, motivation, perceived learning benefits, and instructional language experiences in Kahoot!-based EFL learning, comparing English-only (n=36) and mixed English–Indonesian (n=36) conditions in an Indonesian secondary school. Quantitative data from a 58-item questionnaire and pretest-posttest assessments were analyzed using ANCOVA and regression; qualitative data from 12 semi-structured interviews were thematically analyzed. Descriptive results showed high engagement (M=4.38), motivation (M=4.25), and perceived benefits (M=4.12). The mixed English–Indonesian group demonstrated significant improvement (t(35)=-9.057, p<.001, d=-1.510). ANCOVA confirmed instructional language effects on posttest achievement (F(1,69)=83.201, p<.001, Partial η²=.547). Engagement was the strongest predictor of perceived benefits (R²=.809). Qualitative findings indicated bilingual support improved comprehension, reduced anxiety, and increased response speed, particularly for lower-proficiency learners. Findings suggest pedagogical translanguaging can support participation and achievement in gamified EFL learning, though generalizability is limited by single-site sampling.